Những chiến lược kết thúc hội thoại ở văn phòng giữa nhân viên và người quản lý bằng tiếng Anh và tiếng Việt = Verbal strategies used in closing a conversation at offices by English and Vietnamese staff and managers /Hoàng Trà My. - Hoàng, Trà My.
The study aims to compare and contrast how English and Vietnamese staff and managers verbally end their conversations at offices based on the data from 120 conversations (60 English and 60 Vietnamese) conducted in films. With content analysis, verbal closing strategies are noted down, coded and compared in both languages. The results show that they both frequently use “thank you”, “goodbye” or refer to future actions or contacts in closing sections. However, Vietnamese subjects produce much lengthier closing sections with the employment of more types and numbers of verbal strategies than English ones. Additionally, through the use of verbal strategies, the power distance between Vietnamese staff and managers is displayed more significantly than that of English ones.